Continuous heat release type inorganic waterproof plugging material and preparation method thereof
By using components of components such as sodium oxide and electrolytic iron powder in inorganic waterproofing materials, the effect of rapid hardening and high strength under low temperature conditions in winter is achieved, and the existing materials are slow. The problem improves the anti -seepage of materials and the long -lasting effect of the leakage.
Patent Information
- Application Number
- CN202411160823.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-01-28
AI Technical Summary
Under low-temperature construction conditions in winter, the existing inorganic waterproof leak plugging materials have a long settling time and slow strength, which cannot achieve the effect of rapid leak plugging. Commonly used coagulant agents will lead to loss of late-stage strength and waterproof performance of the material.
Using continuous heat -draining inorganic waterproof materials, quickly release heat through sodium oxide and water reactions, combined with the original battery formed by electrolytic iron powder, activated carbon and chlorine salt to slowly heat up, promote cement hydration response, and improve the material of the material Power and anti -permeability.
In winter, the condensation time and upper intensity time of inorganic waterproofing materials are significantly shortened under low temperature conditions, and the strength and anti -penetration of the material is improved to ensure rapid leakage and long -term effects.
Smart Images

Figure BDA0005006353820000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a continuous exothermic inorganic waterproof plugging material and a preparation method thereof. Background Art
[0002] At present, the inorganic waterproof plugging materials used for rapid arc wiping and leveling in the process of waterproof construction of home decoration are mainly made of sulphoaluminate cement, silicate cement, and coarse aggregate as raw materials, and polymer additives are added to improve the product's impermeability, crack resistance, bonding strength and other indicators. However, this material is greatly affected by temperature. The lower the temperature, the longer the coagulation time required for the material. During winter construction, it is often necessary to wait for several hours before plugging or proceeding to the next process, and the effect of rapid plugging cannot be achieved. At present, coagulants are usually used to shorten the coagulation time of the system. However, the use of conventional coagulants such as lime, sodium carbonate, lithium carbonate and other substances can meet the needs of rapid hardening, but the material's later strength and waterproof performance are greatly lost, and the long-term plugging is insufficient, which still cannot meet the needs of rapid industrial production.
[0003] Therefore, providing an inorganic waterproof plugging material that can harden quickly and has high strength under low-temperature construction in winter has high practical application value. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a continuous exothermic inorganic waterproof plugging material and a preparation method thereof. The prepared inorganic waterproof plugging material can effectively solve the problems of long coagulation time and slow strength gain during winter construction and has good adaptability to the environment.
[0005] The technical solution adopted by the present invention is:
[0006] On the one hand, the present invention provides a continuous exothermic inorganic waterproof plugging material, comprising, by weight:
[0007] 40-50 parts of sulphoaluminate cement, 10-20 parts of silicate cement, 30-40 parts of washed river sand, 0.1-1 parts of water reducer, 0.1-1 parts of cellulose ether, 5-10 parts of rubber powder, 5-10 parts of electrolytic iron powder, 5-10 parts of activated carbon, 0.1-0.2 parts of chloride, 5-10 parts of sodium peroxide, 0.1-1 parts of early strength agent and 0.5-5 parts of lignin.
[0008] The beneficial effects of the present invention are:
[0009] (1) The present invention uses sulphoaluminate cement and silicate cement as cementing materials, and uses sodium peroxide, electrolytic iron powder, activated carbon and chloride salt in combination. When the inorganic waterproof plugging material is mixed with water for use under low temperature conditions in winter, sodium peroxide reacts with water to quickly release a large amount of heat, shortening the coagulation time and strength-up time of the inorganic waterproof plugging material. At the same time, on the one hand, the oxygen released by the reaction and the oxygen in the air form a primary battery with the electrolytic iron powder, activated carbon and chloride salt, and a redox reaction slowly releases heat, providing continuous heat for the inorganic waterproof plugging material, further promoting the coagulation and strength-up effect of the inorganic waterproof plugging material; on the other hand, the sodium hydroxide generated by the reaction can also react with the carbonate in the cement to convert the carbonate into secondary clinker, thereby increasing the strength and impermeability of the inorganic waterproof plugging material. The present invention combines the "rapid heat release" of sodium peroxide with the "slow heat release" of the iron powder primary battery reaction to ensure that the cement hydration reaction can be carried out efficiently at low temperatures, and can complete coagulation in a shorter time and have higher strength.
[0010] (2) In the inorganic waterproof plugging material of the present invention, the electrolytic iron powder is not completely reacted, and the electrolytic iron powder remaining in the cement stone formed by the inorganic waterproof plugging material can improve the compressive strength of the inorganic waterproof plugging material; the activated carbon does not participate in the reaction due to its catalytic effect, and finally remains in the inorganic waterproof plugging material, which can improve the adsorption of formaldehyde, benzene series, etc. on the wall surface, and improve the indoor air quality; the chloride salt can also fill the small gaps in the cement stone during the cement hydration process in the inorganic waterproof plugging material, and the appropriate amount of addition can improve the durability, frost resistance and impermeability of the inorganic waterproof plugging material.
[0011] Preferably, the particle size of the electrolytic iron powder is 120-200 mesh.
[0012] According to the above description, by optimizing the particle size of the electrolytic iron powder, on the one hand, it is ensured that the electrolytic iron powder is fully in contact with oxygen, so that the inorganic waterproof plugging material has the advantages of sufficiently high heat release efficiency and long heat release time; on the other hand, it is beneficial to improve the compressive and flexural strength of the inorganic waterproof plugging material.
[0013] Preferably, the activated carbon is mesoporous activated carbon with a particle size of 120-200 mesh.
[0014] According to the above description, it can be seen that the preferred particle size of activated carbon is beneficial to its adsorption of oxygen, thereby promoting the efficient and continuous progress of the iron powder primary battery reaction.
[0015] Preferably, the chloride salt is at least one of sodium chloride and potassium chloride.
[0016] Preferably, the sulphoaluminate cement is R.SCA 42.5 rapid hardening sulphoaluminate cement;
[0017] The silicate cement is PO 42.5 ordinary silicate cement;
[0018] The particle size of the washed river sand is 40-70 mesh;
[0019] The water reducer is at least one of a naphthalenesulfonate water reducer, a polycarboxylate water reducer and an aminosulfonate water reducer;
[0020] The cellulose ether is one of hydroxypropyl cellulose ether, methyl cellulose ether or hydroxyethyl cellulose ether;
[0021] The rubber powder is styrene-butadiene rubber powder, and its average particle size is 85 μm;
[0022] The early strength agent is nano-scale calcium silicate hydrate;
[0023] The lignin is perfluorosilane-modified lignin.
[0024] According to the above description, the present invention can better improve the comprehensive performance of the inorganic waterproof plugging material by optimizing the types of other components in the system. Among them, by selecting a compound of fast-hardening sulphoaluminate cement and ordinary silicate cement, the characteristics of the former such as fast setting and hardening, high early strength and the latter having better mechanical properties can be fully utilized; by selecting 40-70 mesh washed river sand, it is beneficial to improve the compressive strength of the material and reduce shrinkage; by selecting sulfonate or carboxylate water reducers to adjust the workability of the material and reduce the amount of water added to ensure the strength of the material; by selecting the preferred cellulose ether, the water retention of the material is improved so that more water can participate in the cement hydration process; by selecting styrene-butadiene rubber powder, the flexibility of the material and the bonding strength with the base layer are improved; by selecting nano-scale hydrated calcium silicate as an early strength agent, it can provide an initial nucleation point for cement hydration, reduce the nucleation barrier, shorten the induction period, accelerate the cement hydration process, and achieve the purpose of improving the early strength of the material, and has no adverse effect on the later strength. At the same time, it can also play a synergistic water-reducing role with the water reducer; by selecting perfluorosilane-modified lignin, it can synergistically improve the hydrophobicity of the material with chloride salts to achieve a better waterproof effect. At the same time, its water-reducing effect can reduce the water consumption while improving the strength of the material.
[0025] Another aspect of the present invention provides a method for preparing the continuous exothermic inorganic waterproof plugging material described in any one of the above technical solutions, comprising the following steps:
[0026] S1. Under nitrogen protection, the sulphoaluminate cement and silicate cement are mixed and stirred uniformly;
[0027] S2, continue to add the water reducing agent, cellulose ether, electrolytic iron powder, rubber powder, early strength agent, lignin, activated carbon and chloride salt and mix and stir evenly;
[0028] S3. Finally, add the sodium peroxide and washed river sand, mix and stir evenly, take samples for inspection, and package after passing the inspection.
[0029] Preferably, in each step, the stirring rate is 500-600 r / min, and the stirring time is 3 min. DETAILED DESCRIPTION
[0030] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.
[0031] Example 1
[0032] A continuous exothermic inorganic waterproof plugging material, comprising, by weight:
[0033] 45 parts of sulphoaluminate cement, 15 parts of silicate cement, 35 parts of washed river sand, 0.3 parts of water reducer, 0.2 parts of cellulose ether, 6 parts of rubber powder, 8 parts of electrolytic iron powder, 8 parts of activated carbon, 0.15 parts of chloride, 7 parts of sodium peroxide, 0.5 parts of early strength agent and 3 parts of lignin.
[0034] The particle size of the electrolytic iron powder is 120-200 meshes.
[0035] The activated carbon is mesoporous activated carbon, and its particle size is 120-200 meshes.
[0036] The chloride salt is potassium chloride.
[0037] The sulphoaluminate cement is R.SCA 42.5 rapid hardening sulphoaluminate cement;
[0038] The silicate cement is PO 42.5 ordinary silicate cement;
[0039] The particle size of the washed river sand is 40-70 mesh;
[0040] The water reducer is a naphthalenesulfonate water reducer;
[0041] The cellulose ether is hydroxyethyl cellulose ether;
[0042] The rubber powder is styrene-butadiene rubber powder, and its average particle size is 85 μm;
[0043] The early strength agent is nano-scale calcium silicate hydrate;
[0044] The lignin is perfluorosilane-modified lignin.
[0045] It is prepared by the following method, comprising the following steps:
[0046] S1. Under nitrogen protection, the sulphoaluminate cement and silicate cement are mixed and stirred uniformly at a stirring rate of 500-600 r / min for 3 min;
[0047] S2, continue to add the water reducer, cellulose ether, electrolytic iron powder, rubber powder, early strength agent, lignin, activated carbon and chloride salt and mix and stir evenly at a stirring rate of 500-600r / min and a stirring time of 3min;
[0048] S3. Finally, add the sodium peroxide and washed river sand and mix them evenly at a stirring rate of 500-600r / min for 3min. Take samples for inspection and package them after they are qualified.
[0049] Example 2
[0050] The difference between this embodiment and embodiment 1 is that the dosage of each component is different.
[0051] A continuous exothermic inorganic waterproof plugging material, comprising, by weight:
[0052] 45 parts of sulphoaluminate cement, 15 parts of silicate cement, 35 parts of washed river sand, 0.3 parts of water reducer, 0.2 parts of cellulose ether, 6 parts of rubber powder, 10 parts of electrolytic iron powder, 8 parts of activated carbon, 0.15 parts of chloride, 7 parts of sodium peroxide, 0.5 parts of early strength agent and 3 parts of lignin.
[0053] The rest of the steps remain the same.
[0054] Example 3
[0055] The difference between this embodiment and embodiment 1 is that the dosage of each component is different.
[0056] A continuous exothermic inorganic waterproof plugging material, comprising, by weight:
[0057] 45 parts of sulphoaluminate cement, 15 parts of silicate cement, 35 parts of washed river sand, 0.3 parts of water reducer, 0.2 parts of cellulose ether, 6 parts of rubber powder, 8 parts of electrolytic iron powder, 8 parts of activated carbon, 0.15 parts of chloride, 10 parts of sodium peroxide, 0.5 parts of early strength agent and 3 parts of lignin.
[0058] The rest of the steps remain the same.
[0059] Comparative Example 1
[0060] The difference between this comparative example and Example 1 is that electrolytic iron powder and sodium peroxide are not added. The remaining steps remain unchanged.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 1 is that sodium peroxide is not added. The remaining steps remain unchanged.
[0063] Comparative Example 3
[0064] The difference between this comparative example and Example 1 is that no electrolytic iron powder is added. The remaining steps remain unchanged.
[0065] The inorganic waterproof plugging materials prepared in Examples 1-3 and Comparative Examples 1-3 were uniformly mixed with water at a mass ratio of 1:0.3, and performance tests were performed. The results are recorded in Table 1.
[0066] Table 1
[0067]
[0068] As shown in Table 1, the various indicators of the continuous exothermic inorganic waterproof plugging material prepared by Examples 1-3 of the present invention meet the requirements of GB 23440-2009 Type II standard. Compared with Comparative Examples 1-3, it has the advantages of faster setting time and higher strength, and the surface temperature under the same conditions is higher, the exothermic time is longer, and the low-temperature construction performance is good. Compared with Example 1, since Comparative Example 1 does not contain electrolytic iron powder and sodium peroxide, the surface temperature of the inorganic waterproof plugging material prepared by it at 5°C for 15min and 1h is significantly reduced; Comparative Example 2, which does not contain sodium peroxide only, the surface temperature of the inorganic waterproof plugging material prepared by it at 5°C for 15min is significantly reduced, but the surface temperature of 1h can still maintain a high level; Comparative Example 3, which does not contain electrolytic iron powder only, the surface temperature of the inorganic waterproof plugging material prepared by it at 5°C for 15min is slightly reduced, and the surface temperature of 1h is greatly reduced; at the same time, the impermeability, compressive strength and flexural strength of Comparative Examples 1-3 are all reduced. This shows that the addition of sodium peroxide can release a large amount of heat in a short time, shortening the coagulation and strength-building time of inorganic waterproof plugging materials; at the same time, the addition of electrolytic iron powder and the primary battery formed by activated carbon and potassium chloride can slowly provide supplementary heat for a longer time, synergistically improving the coagulation and strength-building effects of the materials.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A continuous exothermic inorganic waterproof plugging material, comprising, by weight: 40-50 parts of sulphoaluminate cement, 10-20 parts of silicate cement, 30-40 parts of washed river sand, 0.1-1 parts of water reducer, 0.1-1 parts of cellulose ether, 5-10 parts of rubber powder, 5-10 parts of electrolytic iron powder, 5-10 parts of activated carbon, 0.1-0.2 parts of chloride, 5-10 parts of sodium peroxide, 0.1-1 parts of early strength agent and 0.5-5 parts of lignin.
2. The continuous exothermic inorganic waterproof plugging material according to claim 1, characterized in that: The particle size of the electrolytic iron powder is 120-200 meshes.
3. The continuous exothermic inorganic waterproof plugging material according to claim 1, characterized in that: The activated carbon is mesoporous activated carbon, and its particle size is 120-200 meshes.
4. The continuous exothermic inorganic waterproof plugging material according to claim 1, characterized in that: The chloride salt is at least one of sodium chloride and potassium chloride.
5. The continuous exothermic inorganic waterproof plugging material according to claim 1, characterized in that: The sulphoaluminate cement is R.SCA 42.5 rapid hardening sulphoaluminate cement; The silicate cement is PO 42.5 ordinary silicate cement; The particle size of the washed river sand is 40-70 mesh; The water reducer is at least one of a naphthalenesulfonate water reducer, a polycarboxylate water reducer and an aminosulfonate water reducer; The cellulose ether is one of hydroxypropyl cellulose ether, methyl cellulose ether or hydroxyethyl cellulose ether; The rubber powder is styrene-butadiene rubber powder, and its average particle size is 85 μm; The early strength agent is nano-scale calcium silicate hydrate; The lignin is perfluorosilane-modified lignin.
6. A method for preparing the continuous exothermic inorganic waterproof plugging material according to any one of claims 1 to 5, comprising the following steps: S1. Under nitrogen protection, the sulphoaluminate cement and silicate cement are mixed and stirred uniformly; S2, continue to add the water reducing agent, cellulose ether, electrolytic iron powder, rubber powder, early strength agent, lignin, activated carbon and chloride salt and mix and stir evenly; S3. Finally, add the sodium peroxide and washed river sand, mix and stir evenly, take samples for inspection, and package after passing the inspection.
7. The method for preparing the continuous exothermic inorganic waterproof plugging material according to claim 6, characterized in that: In each step, the stirring rate was 500-600 r / min and the stirring time was 3 min.